Implementasi Kebijakan Program Sekolah Rakyat Kementerian Sosial RI (Studi Kasus: Sekolah Rakyat Menengah Atas 10 Jakarta Selatan) - Ibnu, Kautsar Ibnu Muharam; Teguh Kurniawan (Sosio Konsepsia: Jurnal Penelitian dan Pengembangan Kesejahteraan Sosial, 2025)
Poverty and education remain major global issues, particularly in Indonesia. The government has promoted a free, boarding-based education policy through the “Sekolah Rakyat” program, as stipulated in Instruksi Presiden No.8 Tahun 2025. This study aims to analyze the implementation of the Sekolah Rakyat program at SRMA 10 South Jakarta using a qualitative research method.The theoretical framework for implementation refers to George Edward III, which includes four key dimensions: communication, resources, implementer disposition, and bureaucratic structure. The results of the study show that all implementation dimensions function well, particularly in terms of communication and implementer disposition. However, the resource and bureaucratic structure dimensions still face challenges and obstacles in implementation. Furthermore, studies on Sekolah Rakyat remain very limited, as the program was only launched in July 2025. These insights are used to formulate recommendations for policymakers and program implementers to ensure that the Sekolah Rakyat program is implemented effectively in line with its main objectives.